Analisis Hubungan Bilateral Indonesia-Amerika Serikat: Studi Kebijakan Imigran pada Masa Pemerintahan Donald Trump (2017-2021) - Khaeruddin Khaeruddin (Universitas Veteran Bangun Nusantara, 2023)
This paper discusses the bilateral relationship between Indonesia–United States due to immigration policies during the Donald Trump administration in the period 2017-2021 and the immigrant community in the United States and the relationship between the two. The formulation of the problem is what motivates the United States to decide its immigration policy and second is how Indonesia responds to the United States' policy, especially the problem of immigrants from Indonesia. The immigration policy discussed in this paper is the Executive Order signed by Donald Trump in 2017 regarding the ban on people from seven Muslim countries who, according to the United States, are supporting countries. The writing method uses literature study and data presentation or literature review. This paper shows that Donald Trump's immigration policy has an impact on immigrants from seven existing Muslim countries and prospective immigrants who will go to the United States. The impact on the main target, in terms of bilateral relations with Indonesia, did not show a significant effect, although there was a decrease in the number of students studying in the United States of around 17% due to this policy. However, the Indonesian government considers Donald Trump's policy only to maintain security in the United States. Indonesia and the United States after Donald Trump's Immigration policy The US Ambassador asked the Indonesian government that the policy was not aimed at Muslims but for US security to limit immigrants from Indonesia who would receive protection from the Indonesian Embassy in the United States.